Presence of Fertility-associated antigen on sperm membrane corresponds to greater freezability potential of Frieswal bull semen - PANDE, MEGHA; SRIVASTAVA, N; SONI, Y K; OMERDIN, OMERDIN; KUMAR, M; TYAGI, S; SHARMA, ANKUR; KUMAR, SURESH (The Indian Journal of Animal Sciences, 2018)
Several studies have shown relationship of semen freezability with Fertility-associated antigen (FAA) in purebreds. Objectives of present investigation were to determine presence of FAA in Frieswal bull semen and its relationship with freezability. Study involved separation of seminal plasma (SP, FAA – or +) and sperm membranes (SM, FAA – or +), electrophoresis, protein content and quality assessment (n=36).Five groups were: Group-I (19.4%, SP+ve/SM+ve); Group-II (22.2%, SP-ve/SM+ve); Group-III (25%, SP+ve/SM-ve); Group-IV (16.7%, SP-ve/SM-ve), and Group-V (16.7%, unprocessed, initial progressive motility ≤30%, negative control).At postthaw stage, Group-I and -II showed significantly higher (p< 0.001) freezabilitythan FAA-SM-ve groups. Moreover, Group-III with FAA in seminal plasma but not on membrane showed better post-thaw motility than Group-IV, which totally lacked FAA. Our results have shown that 28–30 kDa protein is present in SP and SM of majority of Frieswal bulls and presence of FAA in SM confers appreciable improvement in freezability.